Critical behaviour of the MHD flow in convergent-divergent channels - Alam, Md. Sarwar; Khan, Md. Abdul Hakim (Journal of Naval Architecture and Marine Engineering, 2011)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–> The effect of external Magnetohydrodynamic (MHD) field on the steady two-dimensional nonlinear flow through Convergent-Divergent Channels of a viscous incompressible electrically conducting fluid is investigated. We compute the critical behaviour of the solution govern by the equation. Our approach uses the power series in order to observe the instability of the problem. The series is then summed by using various generalizations of the approximants. We find the critical values of various parameters and type of the principal singularity for different choice of MHD effect. DOI: 10.3329/jname.v7i2.5635